Capital Buffer dan Faktor Penentunya di Indonesia - Abel Tasman (Universitas Negeri Padang, 2020)
Capital buffer is defined as the difference between the bank's capital ratio and the capital adequacy ratio (Capital Adequacy Ratio) or CAR imposed by the Central Bank. Capital buffers can be used as capital reserves in times of various economic shocks so as to minimize risks faced by banks. A bank that has a high capital buffer reflects a high CAR as well, while a CAR that is too high is also not profitable for the bank, because this capital should be used for lending and investing in an effort to maximize profits. This study aims to determine the determinants of going public banking capital buffer in Indonesia for the period 2014 to 2018. The sample selection is based on purposive. Acting as the dependent variable is the capital buffer and the independent variables are ROE, NPL, Lag of capital buffer (〖BUFF〗 _ (t-1)), Size and GDP. This study used multiple regression analysis. The results of this study indicate that the selected determinants of the capital buffer of going public banking in Indonesia are adjustment costs and the business cycle. Adjustment costs have a positive and significant effect on the capital buffer of going public banking in Indonesia and the business cycle has a negative and significant effect on the capital buffer of go public banking. public in Indonesia. Thus, the sample companies can optimize their capital buffer which can be ideal in order to maximize profits by considering the two factors above.